Твори класиків української літератури у репертуарі ніжинських театрів другої половини ХХ ст. - Рой, С.В. (Сіверщина в історії України, 2023)
У статті здійснено спробу дослідити інтерес до класичної літературної спадщини у творчому доробку ніжинських театрів другої половини ХХ ст., прослідкувати процес пошуку ніжинськими корифеями театру національної ідентичності в сценічному мистецтві та зростаючу потребу публіки до творів українських письменників. Дослідження базується на систематизації та вивченні джерел з історії театрального мистецтва, наявних у фондах НКМ ім. І. Спаського. До них належать фотографії, газетні статті та афіші, які можна розглядати як достовірні джерела, що містять точну інформацію про репертуар театрів, склад його трупи, виконавців тієї чи іншої вистави. The article attempts to investigate the interest in the classical literary heritage in the creative work of Nizhyn theaters in the 2nd half of the 20th century To follow the process of search by Nizhyn luminaries of theatrical art, national identity in stage art and the growing need of the public for the works of Ukrainian writers. The research process will be based on the systematization and study of historical sources on the history of theater art, available in the funds of the NKM named after I. Spasskyi. These include photographs, newspaper articles and posters, which can be considered as reliable sources containing accurate information about the repertoire of theaters, the composition of its troupe, performers of a particular performance. In the second half of 20th century, not only the interest in the classical literary heritage became very noticeable in the creative work of Nizhyn theaters in the 2nd half of the 20th century, but also during the period when it was included in the main part of the repertoire of theater troupes, both professional and amateur. The most popular were the works of T.H. Shevchenko, I.Ya. Franko, M. Kropyvnytskyi, H. Kvitka-Osnovianenko and others. There was a growing need of theater luminaries and the public for the national cultural heritage, including the theatrical one. This thesis is fully confirmed by the available sources from the history of theater art, in the funds of the NKM named after I. Spasskyi and archival sources. They include photographs, newspaper articles, posters, tour reports, and programs of performances, which can be considered as reliable sources containing accurate information about the repertoire of theaters, the composition of its troupe, performers of a particular performance.